MENINGKATKAN KEMAMPUAN MENYELESAIKAN MASALAH PENGOLAHAN LIMBAH BERDASARKAN GAYA KOGNITIF SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Haryati, Ani; Sholahuddin, Arif (Vidya Karya Jurnal Kependidikan, 2015)
It has been conducted the class action research that aims to improve students ability in solving problems based on cognitive style, social interaction, understanding of concepts, and the psychomotor skills by using models of Problem Based Learning (PBL). This classroom action research conducted Â by using 2 cycles. The subjects were 33 of eleventh grade students ofÂ the Nurses Health Program of SMK 1 Murung Pudak Tabalong. The research instruments were observation sheet of teachers and students activities, responses questionnaire, students assessment, problem solving skills asessment, social interaction skills assessment and psychomotor skills assessment. The result showed that the application of PBL (1) improve students ability to solve the problem on the competence of waste treatment (2) improve student social interaction (3) enhance the students understanding of the material waste processing. (4) psychomotor skills of students in carrying out the experiment reached the category of